KEPUASAN PERNIKAHAN DAN KEMATANGAN EMOSI PADA SUAMI DENGAN ISTRI BEKERJA - Nurhikmah Nurhikmah; Hepy Wahyuningsih; Fitri Ayu Kusumaningrum (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2018)
This study explore the correlation between marital satisfaction and emotional maturity among husbands with working wife. The hypothesis to be tested is there is positive correlation between marital satisfaction and emotional maturity. Participants in this research were husbands aged 20-70 years old with working wife.  The Indonesian Moslem Marital Quality Scale from Wahyuningsih (2013) and emotional maturity scale from Singh and Bhargava (Kathuria, 2014) were used in this study. The data was analyzed by product moment analysis technique. Result showed that marital satisfaction was significantly correlated with emotional maturity (r =0,223, p<0.05).